Distribution of TERT Alternative Splicing (AS) variants in pediatric brain tumors - Mascaro-Cordeiro, Bruna; Dias Oliveira, Indhira; Santos, Gianni Mara Silva dos; Valim, Gabriela Rampazzo; Saba-Silva, Nasjla; Capellano, Andrea Maria; Cavalheiro, Sergio; Dastoli, Patrícia Alessandra; Alves, Maria Teresa de Seixas; Toledo, Silvia Regina Caminada de (European Journal of Oncology and Environmental Health, 2018)
Introduction: The mechanism of telomerase regulation remains unclear, but has been suggested that TERT (telomerase reverse transcriptase) is regulated by alternative splicing (AS). Besides the full-length (FL) transcript, alternatively spliced variants have been described within the reverse transcriptase domain of TERT including, deletion alpha (α), beta deletion (β-), and alpha beta deletions (α-β-). Medulloblastoma (MB) and Ependymoma (EP) are two of more frequent brain tumors of childhood. We investigated and described the principal TERT transcripts; FL, α-, β- and α-β-, and whether or not the presence of these patterns could be associated to clinical pathological characteristics and survival of pediatric EP e MB. Methods: We selected 58 MB and 43 EP samples. TERT AS variants were amplified by nested PCR (polymerase chain reaction) and the amplified products were electrophoresed on 2% agarose gel. Results: In general, around 5% of the samples of each group of tumors exhibited exclusively FL variant. TERT variants with deletion, exclusively or combined with others patterns, were detected in 70% of MB and 39% of EP tumors. 27% of MB and 60% EP did not show any of the patterns. We did not observed significant association between TERT splicing variants and clinical pathological characteristics of MB e EP tumors. Discussion: Since FL transcript is the only associated with reverse transcriptase activity, our results suggest that the association of TERT mRNA expression to clinical pathological characteristics of patients must be analyzed with caution. Further investigations will help to elucidate the complex mechanism involving AS of TERT gene and the function of deleted variants in tumorigenesis of pediatric brain tumors.